2022
DOI: 10.3390/life12040505
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening of the Natural Product Osthole and Its Derivates for Anti-Inflammatory Activity

Abstract: Osthole (OS) is a natural coumarin with a long history of medicinal use in a variety of diseases, such as itch and menstrual disorders. In recent years, OS has been shown to treat inflammation and reduce the expression and activity of NF-κB, although its mechanism of action is still unclear. Overexpression of inflammatory cytokines can have many negative effects in the body, including inducing preterm labor; thus, the modulation of inflammation by OS and its derivatives may be able to delay preterm birth, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Osthole ( 1 , Figure ), known as methoxy parsley, belongs to the coumarin-type compounds and has a high content in the plant Cnidium monnieri, , which possesses antitumor activity, , anti-inflammatory activity, , neuroprotective effect, and other biological properties. , Recent studies have found that it has potential application value in agriculture. , According to the China Pesticide Information Network (), 20 different osthole-type fungicides and insecticides were registered in China. In recent years, structural optimization of natural products as precursors has become the crucial means to obtain pesticide candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Osthole ( 1 , Figure ), known as methoxy parsley, belongs to the coumarin-type compounds and has a high content in the plant Cnidium monnieri, , which possesses antitumor activity, , anti-inflammatory activity, , neuroprotective effect, and other biological properties. , Recent studies have found that it has potential application value in agriculture. , According to the China Pesticide Information Network (), 20 different osthole-type fungicides and insecticides were registered in China. In recent years, structural optimization of natural products as precursors has become the crucial means to obtain pesticide candidates.…”
Section: Introductionmentioning
confidence: 99%